1997
DOI: 10.1063/1.119878
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer organic electroluminescent devices by vapor deposition polymerization

Abstract: A novel method is presented herein regarding the preparation of a single-layer organic electroluminescent (EL) polymer thin film device. The device was made by simultaneously co-depositing two polymer thin film forming monomers, a hole-transporting molecule triphenyldiamine derivative (TPD) and an EL active molecule 1,1,4,4-tetraphenyl-1,3-butadiene (TPB) on an indium-tin-oxide (ITO) glass substrate. The device structure was composed of the ITO glass, the TPD, and TPB co-doped polymer thin film, and a thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…These contribute to the broad emission and to the shoulder at about 2.75 eV observed in the cw spectra. We point out that the PL data reported in the literature [18][19][20][21][22][23][24] do not allow distinguishing between the intrinsic emissions and the emission from defect states, the observed PL being typically unpolarized, relatively broad, and centred between about 2.7 and 2.8 eV, depending on the sample.…”
Section: Spontaneous and Amplified Spontaneous Emissionmentioning
confidence: 90%
See 4 more Smart Citations
“…These contribute to the broad emission and to the shoulder at about 2.75 eV observed in the cw spectra. We point out that the PL data reported in the literature [18][19][20][21][22][23][24] do not allow distinguishing between the intrinsic emissions and the emission from defect states, the observed PL being typically unpolarized, relatively broad, and centred between about 2.7 and 2.8 eV, depending on the sample.…”
Section: Spontaneous and Amplified Spontaneous Emissionmentioning
confidence: 90%
“…[22,23] Furthermore, it can be deposited in thin film form on different substrates. [18][19][20][21][22] The photoluminescence (PL) properties of the TPB molecules in solution and in optically transparent polymeric matrices have been investigated both experimentally [24] and theoretically, [25] and the emission spectrum of TPB-based devices is reported by many authors, with maximum typically found at 2.7-2.8 eV and relatively high emission quantum yield. [18,19,21,23,24] Interestingly for both applications and for the comprehension of the intrinsic properties, TPB forms single crystals.…”
Section: à2mentioning
confidence: 98%
See 3 more Smart Citations